'Because I point to myself as the hog': Interactional achievement of moral decisions in a classroom. (June 2016) - Niemi, Kreeta
Abstract: Drawing on the conversation analytic and sociocultural perspectives, this study investigates children's situated moral negotiations in classroom peer interaction in the absence of a teacher. The conversation analytic methodology is used to operationalise some of the key elements of the sociocultural perspective on moral development. In this way, this study enables readers to observe and study the semiotic, conversational and interactional mediations of moral functioning in real life, with the example of children's moral practices. The empirical analysis is based on video-recorded sequences in which primary school children work with the rules of a counting rhyme which is banned by their teacher. With the use of multisemiotic meaning-making resources the children constructed a subgroup of different counting rhyme rules to the overarching teacher-advised rules while reciting the rhyme. By doing this, the children showed a will to comply with their teacher's moral stance, but at the same time, they extended their moral autonomy and ownership over their actions and maximised the shared fun. Thus, children's capacity to be collaborative and playful highlights their competence for moral autonomy and responsibility. Highlights: This study provides a novel contribution to research on children's morality. Study dealt with children's situated moral negotiations in classroom peer interaction. Moral work was an intersubjective process using words and multisemiotic resources. Moral cognition was distributed across social relationships and cultural artefacts. Shared frames of reference are important aspects of intersubjectivity.